Social context may affect urinary excretion of 11-ketotestosterone in african cichlids - Hirschenhauser, Katharina (2012)
We previously investigated the androgen responsiveness of males to simulated partner and territory intrusions in five African cichlid species (Neolamprologus pulcher, Lamprologus callipterus, Tropheus moorii, Pseudosimochromis curvifrons, Oreochromis mossambicus; Hirschenhauser et al., 2004). Here we re-analysed data on 11-ketotestosterone (11-KT) levels in holding water to compare the free (presumably from the gills) and conjugated (presumably from urine and faeces) 11-KT fractions. We sampled (i) pre-test baseline control levels from individual males in social isolation and (ii) response levels released after social interactions, either with an ovulating female or a male territory intruder. In four out of five species, conjugated metabolites contributed to the observed total 11-KT responses in water during social context, which was particularly apparent in peak responsive individuals exposed to male intruders. Thus, in water from males sampled in isolation immunoreactive 11-KT seemed to derive both from gills and urine, whereas the urinary 11-KT component apparently increased in the social context, particularly when a male was challenged by a same-sex intruder. These results suggest that (i) the social context may affect urine release patterns of males and (ii) 11- KT data acquired by using fish-holding water may not simply reflect the passive transmission of steroid hormones via the gills.